Use of fabricated germanium-doped optical fibres for radiotherapy postal dose audit of megavoltage photon beams under non-reference conditions in selected Malaysian radiotherapy facilities - Ahmad Fadzil, Muhammad Safwan (2020)
The thermoluminescence dosimetry (TLD) postal dose audit programmes are being conducted in hospitals to assure a proper calibration of the radiotherapy machines and maintain a high degree of accuracy and consistency in clinical dosimetry. As radiation delivery techniques become more complex such as Intensity Modulated Radiation Therapy (IMRT) and Volumetric Modulated Arc Therapy (VMAT), auditing programmes must evaluate various aspects of the delivery technique to provide a reasonable assurance that a radiotherapy centre performs a particular treatment as per best practice. Therefore, to adapt this new delivery approach, International Atomic Energy Agency (IAEA) was recently introduced a methodology for postal dose audits under non-reference conditions using a phosphor-based dosimeter. However, due to limited performances, the focus of interest in dosimetry application has shifted to optical fibre dosimetry where the fabricated optical fibre has been developed as a potential remote dosimeter due to their favourable physical and dosimetric characteristics. This presents works established the dosimetric characteristics of fabricated germanium (Ge) doped cylindrical fibre (CF) and flat fibre (FF) with elevated Ge dopant concentrations (6, 8 and 10 mol%) which come in various sizes for radiotherapy postal dose audits under non-reference conditions. The thermoluminescence (TL) performance of CF and FF was extensively studied including dose linearity, reproducibility, repeatability, fading, energy-, dose rate-, and angular dependence. Details on TL kinetic parameters of CF and FF were investigated comprehensively using the computerised glow curve deconvolution (CGCD) analysis in order to figure out the glow peak kinetic parameters including maximum peak temperature (Tmax), activation energy (Ea) and peak integral (PI). A methodology for absorbed dose measurements by CF, FF and TLD-100 powder together with uncertainties budget were established with several correction factors were applied. A preliminary study was conducted to study the variation between absorbed doses measured by CF and FF over TLD-100 powder. The first Malaysian national postal dose audit programme under non-reference conditions based on the fabricated Ge-doped optical fibres system was carried for two photon beams: 6 MV and 10 MV involving ten radiotherapy centres. The measurements of the absorbed dose were made using three types of TLD, comprised of CF, FF and TLD-100 powder. The setup was based on the IAEA postal dosimetry audit under non-reference conditions protocols using a modified TLD holder. The investigation on basic dosimetric characterisations of various sizes of fabricated Ge-doped optical fibres found that the 483 μm-diameter fabricated Ge-doped cylindrical fibre (CF) and 85 μm × 270 μm-dimension fabricated Ge-doped flat fibre (FF) satisfy numerous TL characteristics to be introduced as a potential TL dosimeter in radiotherapy dosimetry including linear dose-response (1 up to 10 Gy), minimal energy dependency, reproducibility less than 5% and moderate TL fading (less than 30% over 22nd days post-irradiations). A further detailed study on different dopant concentrations revealed that the responses of the fabricated Ge-doped optical fibres were intensified with decreasing in Ge dopant concentrations. The greatest TL signal being obtained was by a 6 mol%, followed by a 8 mol% and a 10 mol% fabricated Gedoped optical fibres. Therefore, a 6 mol% Ge-doped 483 μm-diameter CF and 85 μm × 270 μm-dimension FF were chosen to be employed in the radiotherapy postal dose audit program under non-reference conditions. CF and FF show linear dose-response from 100 cGy up to 300 cGy with the coefficient of determination (R²) more than 0.99 for both 6 MV and 10 MV photon beams. CF and FF also found to have good TL reading reproducibility and repeatability (±5%). The TL response of the optical fibres was independent of the irradiation angle and dose rate. The maximum fading rate after 106th days post-irradiation was found to be at 37.6% and 63.4% for CF and FF respectively. Glow curve study and kinetic parameters analysis revealed that CF appears as a single broad peak while FF represents two peaks system. The hightemperature half of the peak is slightly broader than the low temperature one, indicates the possibility of strong electron re-trapping. The absorbed dose formalism using fabricated Ge-doped optical fibres were established with several correction factors included such as individual capsule-, energy-, holder- and fading correction factors. The uncertainties analysis revealed that CF, FF and TLD-100 powder have combined uncertainty of 4.30%, 5.56% and 0.74% respectively for 6 MV photon beams while 4.31%, 5.57% and 0.80% respectively for 10 MV photon beams. The preliminary pilotaudit study for absorbed dose measurement under non-reference conditions demonstrated there are no significant differences (p > 0.05) between absorbed dose measured by CF, FF and TLD-100 powder. The results of the postal dose audit conducted for non-reference conditions involving ten radiotherapy centres demonstrate that after repeated measurement, the mean distribution for CF, FF and TLD-100 powder are 1.00, 0.99 and 0.98 respectively. Several causes of the deviations of absorbed dose measurements are identified during audit programmes such as incorrect monitor unit (MU) calculation, accidental switch of dosimeter capsules position and incorrect wedge orientation. In conclusion, it was found that fabricated Ge-doped optical fibres are feasible to be introduced as a potential dosimeter for postal dose audits with appropriate correction factors applied to the absorbed dose measurements. Furthermore, these postal dose audits show the importance of external dose audits in radiotherapy centres in identifying the problem in radiotherapy clinical practice and resolving discrepancies that are discovered.